Visionary Leadership and Staff Innovative Behaviour in Public Colleges of Education In Kwara State, Nigeria - Jibola Kadir, Abdullahi Nimota; Adebayo, Tijani Abdulganiyu; Olumide, Sofoluwe Abayomi (International Journal of Education, 2020)
Staff innovative behaviour is critical for organisations if they wish to survive and continue expanding effectively. This study investigated the effect of visionary leadership on staff innovative behaviour in Kwara State, Nigeria. The objective of this study is to examine the relationship between visionary leadership and staff innovative behaviour in Kwara State-owned colleges of education. Quantitative research design was used for the study. A sample of 220 respondents were randomly selected from the sample colleges of education with the use of Research Advisor (2006) table to determine sample size of known population. Pearson correlations and linear regression analysis were used to analyze the collected data. The results show that leadership empowerment, intellectual stimulation, and adaptiveness were positively and significantly correlated with staff innovative behaviour. The result also shows that staff innovative behaviour can be influenced by visionary academic leaders.  It was therefore recommended that academic leaders should continue to boost up the style of leadership empowerment, intellectual stimulation as well as adaptiveness towards the realization of staff innovative behaviour